2018
DOI: 10.7150/ijbs.24624
|View full text |Cite
|
Sign up to set email alerts
|

Integrated multifactor analysis explores core dysfunctional modules in autism spectrum disorder

Abstract: Autism spectrum disorder (ASD) is a complex neurodevelopmental disease in early childhood, and growing up to be a major cause of disability in children. However, the underlying molecular mechanism of ASD remains elusive. Hence, we represented integrated multifactor analysis exploring dysfunctional modules based on RNA-Seq data from corpus callosum in 6 patients with ASD and 6 normal individuals. According to protein-protein interactions (PPIs) and WGCNA, we performed co-expression modules analysis for ASD-asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…We defined elements as the pivot elements which significantly regulated the module as those that fulfilled the following criteria 12 : ≥ 2 relationships between the module and the element; the number significantly enriched targets per module (hypergeometric test, p < 0.05). …”
Section: Methodsmentioning
confidence: 99%
“…We defined elements as the pivot elements which significantly regulated the module as those that fulfilled the following criteria 12 : ≥ 2 relationships between the module and the element; the number significantly enriched targets per module (hypergeometric test, p < 0.05). …”
Section: Methodsmentioning
confidence: 99%
“…However, the molecular mechanism of ASD is unclear. Huang et al analyzed the RNA-sequence data from corpus callosum of six patients with ASD and six normal individuals 21 . The co-expression module analysis for ASD-associated genes showed that the detected DEGs and ncRNAs were significantly involved in nervous system, sensory system, immune system, and organ development.…”
mentioning
confidence: 99%